Math, asked by rohit488, 1 year ago

plzzzzz solve Q15 plzzzzzzzzz

Attachments:

Answers

Answered by jish4you
0
 Hi Rohit,

use (a-b)^2 = a^2 + b^2 - 2ab formula.
and expand both terms

(2x- 1/3)^2 = 4x^2 + 1/9 -4x/3
(x- 5/3)^2 = x^2 + 25/9 -10x/3

now its simple subtraction from here as given in the question
(2x- 1/3)^2 - (x- 5/3)^2
= ( 4x^2 + 1/9 -4x/3 ) - ( x^2 + 25/9 -10x/3 )
= (4x^2 - x^2) + (1/9 - 25/9) + (-4x/3 -(-10x/3) ) )
= 3x^2 - 24/9 + 6x/3
= 3x^2 + 2x - 8/3

hope it helped you.
Please let me know if any further doubt.





Anonymous: no one will understand it
Anonymous: u did totally wrong
jish4you: 3x^2 + 2x - 8/3 is the final answer
Anonymous: ok wait
Anonymous: i m asking a question with my own answer
jish4you: @rohit did u understand ?
rohit488: is it correct
jish4you: yes it pls follow the stepwise
jish4you: @rohit let me know where u cuould not understand ? which step ?
jish4you: @rohit hope its clear now?
Similar questions